Prognostic impact of gene alterations via homologous recombination DNA repair gene alteration status in pancreatic ductal adenocarcinoma - Kawanaka, Yusuke; Inagaki, Chiaki; Okura, Masaki; Mitani, Seiichiro; Takahama, Takayuki; Yonesaka, Kimio; Chiba, Yasutaka; Nakagawa, Kazuhiko; Kawakami, Hisato; Hayashi, Hidetoshi (Frontiers in Medicine, 2025)
BackgroundPancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies, with limited treatment options and poor prognosis. Recent advances in cancer genomic analysis enable the identification of actionable gene alterations, opening new opportunities for personalized therapy. Among these, homologous recombination DNA repair (HRR) gene alterations are associated with distinct biological behavior, favorable prognosis, and increased sensitivity to platinum-based chemotherapy. However, the prognostic impact of coexisting mutations in key driver genes—KRAS, TP53, CDKN2A, and SMAD4—within HRR-altered PDAC remains poorly understood.MethodsWe retrospectively analyzed PDAC patients who underwent genomic profiling testing with FoundationOne® CDx between June 2019 and December 2021 through the Center for Cancer Genomics and Advanced Therapeutics (C-CAT) database. We compared the prevalence and prognostic significance of key gene alterations between HRR-altered and HRR–wild-type (WT) tumors.ResultsOf 2,381 PDAC patients, 274 (11.5%) harbored HRR alterations. These patients showed significantly longer overall survival (OS) than those with HRR-WT tumors (HR = 0.66, p = 0.002). The frequencies of KRAS, TP53, and CDKN2A mutations were less frequent in HRR-altered tumors. TP53 mutation was independently associated with poorer OS across both HRR subgroups, while CDKN2A alteration was a poor prognostic factor in HRR-WT tumors. Interestingly, SMAD4 alteration was linked to improved survival in the HRR-altered group.ConclusionHRR-altered PDAC has a distinct genomic profile and is associated with a favorable prognosis. Our findings demonstrate that coexisting alterations are significant prognostic factors in both HRR-altered and HRR–wild-type tumors. These results highlight the clinical relevance of incorporating comprehensive genomic profiling into routine care to stratify patient prognosis better and inform individualized treatment strategies in PDAC.